Mobile-Web System for friends recommendation in NTU - Chang, Jun Hao (2019)
Social media plays a big part in most people’s life for people to mingle and get to know each other over the internet. Social media application that specialise in letting user to get to find and associate with new people that have similar interest or inclination; are becoming more popular for people to get to know others as society distance itself with mobile user always engross onto their social media and other phone apps. In school, there many opportunities for students to get to know one another; Like orientation camps, career talks, events, classes, etc. The internet platform can be leveraged to provide even more opportunities for students to befriend among themselves. This report examines some existing works and showcase the development of mobile application for a mobile and web system for friends recommendation in Nanyang Technological University.